Retail price rigidity in perishable food products: a case study - Perez-Mesa, J. C.; Galdeano-Gomez, E.; Aznar-Sanchez, J. A. (Spanish Journal of Agricultural Research, 2010)
Why are retailers less likely to vary sale prices of food products when the price paid to the farmer falls than when it rises? As far as perishable goods are concerned, this behavior is usually related to the retailer’s bargaining power. With a view to analyzing the question in greater depth, this study presents a simplified framework considering an ideal scenario in which the retailer wishes to maintain balanced profits due to external pressures or other factors, such as a competitive distribution market. In the face of changing supply, the price-fixing decision of the distributor may also depend on the risk, measured by the relationship between demand elasticity and variable costs, as a result of uncertainty in consumer response to price variations. The simulation of these scenarios is carried out taking as reference the Spanish tomato market. The results of these applications allow to see that despite a relaxation of bargaining power, price asymmetry is not avoided. This work shows the difficulty for suppliers and retailers to reach agreements which could result in competitive advantages.